355 Nationwide occupational medicine training program in the finnish institute of occupational health. (24th April 2018) - Stengård, Jari H; Helaskoski, Eva
Abstract : Introduction: Teaching of occupational medicine is an integral part of the training of occupational health specialists. This training takes place in Finnish Institute of Occupational Health Institute (FIOH) in Helsinki and its four regional offices. A challenge is that instructors in different regions have different skills and their resources are different. Here we present our new, nationwide occupational medicine training program, which has recently piloted and launched. It consists of six modules that correspond to the learning objectives given in university curricula. Each module includes lectures, workshops and self-study but also practical tasks, such as workplace visits, outpatient work and literature search. In teaching we use a web-based learning platform. Methods: The program was developed in collaboration with a selected group of trainees and all instructors in Helsinki and in all regional offices of FIOH. Feedback from instructors and trainees was collected by employing a web-based questionnaire and face-to-face discussions. Results: Feedback from instructors and trainees has been positive. The following things are considered as benefits of the new program: trainees receive same kind of training, regardless of locations where they specialise, they can view lectures later on video and they can discuss with other trainees and instructors in other areas, and instructors can take advantage of each other's material, we can employ modern pedagogic theories and teaching methods and instructors can more easily communicate with their trainees. Discussion: We had a need to reform and unify occupational medicine training at FIOH. Participation of students and all regional instructors was central to the success of the program development. Our program has been well received by trainees and instructors. Web-based learning platform makes it possible for us to take advantage of instructors' different skills and to use new pedagogical theories and methods in our teaching